Persamaan Gender Perempuan Aceh yang Berorientasi Nilai Religius dan Kolektifitas Budaya - Azis, Abdul; Husaini, Husaini; Sanusi, Sanusi; Amiruddin, Amiruddin; Nurasiah, Nurasiah (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2025)
This research aims to explore and examine the role of Acehnese women throughout history, in the political, social, and cultural spheres, by positioning them as active subjects who contribute to the dynamics of society. This research is important because the history of Aceh shows the presence of prominent female figures, such as sultanahs, female scholars, and warriors, who made significant contributions to the sustainability of Acehnese society's identity and social structure. This research uses a qualitative method with a historical-interpretive approach that seeks to understand the traces of women's roles thru narrative analysis, archival documents, literature, and oral testimonies. Data was obtained thru in-depth literature studies of historical manuscripts, local chronicles, colonial archives, and semi-structured interviews with historians, academics, and community figures in Aceh who understand the role of women in local history. The research sample involved 12 key informants who were purposefully selected due to their involvement in historical studies or because of a strong oral tradition heritage in their environment. Data analysis was conducted by reducing information, presenting narratives, and thematic interpretations, resulting in a comprehensive picture of women's position in the historical trajectory of Aceh. The research findings indicate that Acehnese women are not only present in the domestic sphere but also play a significant role in political leadership, the fight against colonialism, and the transmission of cultural and religious values. This finding confirms that the history of Aceh cannot be fully understood without presenting the narrative of women as agents of change. This research contributes to enriching Indonesian historiography with a gender perspective and opens space for a more inclusive and equitable reinterpretation of history regarding women's contributions.